A Qualitative Study On Patients With Chronic Migraine With Medication Overuse Headache: Comparing Frequent And Non‐Frequent Relapsers. Issue 9 (20th August 2018) - Scaratti, Chiara; Covelli, Venusia; Guastafierro, Erika; Leonardi, Matilde; Grazzi, Licia; Rizzoli, Paul B.; D'Amico, Domenico; Raggi, Alberto
Abstract : Background: It is common clinical experience that, after structured withdrawal, some patients with chronic migraine and medication overuse headache (CM with MOH) are more prone than others to relapse and to be in need of further structured treatments. Our aim was to explore similarities and differences between frequent relapsers (FRs) and non‐frequent relapsers (NFRs) by considering their point of view, perceptions, and perspective of their subjective experience with relapse into CM with MOH. Methods: Patients were consecutively recruited on occasion of a structured withdrawal treatment and were interviewed individually about their headache experience and their perspectives on relapse into CM with MOH. We considered FR those patients requiring 2 or more structured withdrawals for MOH within 3 years. A narrative approach with no preconceived coding schemes was employed. To facilitate coding, categorization and organization of data the software QRS NVivo 11.0 was used: themes were defined as common to FR and NFR, or peculiar (by frequency or content) to one of the 2 groups. Results: Sixteen patients (13 women; mean age of 53) were interviewed: 7 were classified as FRs. A total of 22 themes emerged from 552 single quotations (the 10 most relevant covered 82% of the entire body of quotations). Four themes were commonly reported by both FR and NFR patients, and 6 were peculiar to one group only. Common aspects included issues connected to the dilemma between disclosing, concealing and the feelings of isolation around MOH, the idea of being addicted to medication, presence of anxiety, and the attempt to use non‐pharmacological therapies as an alternative to medication. Peculiar aspects included causal attribution (FRs attributed headache to uncontrollable factors); future expectations at the time point of withdrawal (FRs were generally resigned); high‐performance functioning (FRs believed they are "forced" to reach high levels of performance as a consequence of others' inability); coping strategies (FRs tended to "passively accept" problems and showed avoidance‐related behaviors). Moreover, FRs were less frequently aware of their problems and described more frequently depressive symptoms. Conclusions: Our results highlight that some differences between FR and NFR patients with CM and MOH exist. Frequent relapsers among patients with CM and MOH reported some important peculiarities of the lived experience of having chronic migraine; clinicians should recognize these psychosocial aspects such as social relationships, future expectations, the experience of illness, medication management, and how the withdrawal experience is regarded, as they may be associated with frequent relapse into MOH.